PPO.22 Antenatally detected 'short long bones' and 'intrauterine growth restriction' (IUGR) – a comparison of outcomes. (9th June 2014) - Perry, PD; Budd, JLS; Draper, ES
Abstract : Objective: To evaluate the outcome of 342 pregnancies reported antenatally with short long bones (SLBs) or IUGR to the East Midlands and South Yorkshire Congenital Anomaly Register (EMSYCAR) over a five year period (2008–2012). Background: SLBs and IUGR are 'soft' markers identified during pregnancy with potentially serious outcomes of skeletal and chromosomal abnormalities. The extent of the overlap between the two markers is unclear. Methods: Between 2008 and 2012, 377, 652 births were monitored by EMSYCAR. All anomalies reported in pregnancies within the region were coded to ICD-10; all soft markers were coded according to a protocol agreed by the British Isles Network of Congenital Anomaly Registers. Results: 227 cases were identified antenatally with SLBs (6.01/10, 000) and 115 cases with IUGR (3.05/10, 000) including 13 cases that reported both. 32 (14.1%) of the SLBs cases had a chromosomal anomaly, 75 (33.0%) an isolated skeletal anomaly, 21 (9.2%) a serious non-skeletal anomaly, 41 (18.1%) had both and 58 (25.6%) completely resolved. 20 (17.4%) of the IUGR cases had a chromosomal anomaly, 19 (16.5%) an isolated skeletal anomaly, 36 (31.3%) a serious non-skeletal anomaly, 24 (20.9%) had both and 16 (13.9%) fully resolved. Conclusion: An antenatal diagnosis of SLBs appears more indicative of an isolated skeletal anomaly than IUGR; the reverse is true for non-skeletal anomalies. Although SLBs are more widely reported antenatally, the proportion that resolved before delivery (25.6% C. I. 20.0; 31.7) is almost twice that of IUGR cases (13.9% C. I. 8.1; 21.6), strongly suggesting the latter indicates a poorer overall prognosis at birth.